Global Higher Education Forum (GHEF), Malaysia 2007. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
On 6th and 7th November 2007, the National Higher Education Research Institute (IPPTN), Ministry of Higher Education Malaysia and International Association of Universities (IAU), supported by Universiti Sains Malaysia, successfully organised The Global Higher Education Forum (GHEF), Malaysia 2007 at Hotel Nikko, Kuala Lumpur. GHEF 2007 gathered policy-makers, higher education researchers and experts from all over the world to deliberate on higher education issues with a view to sharing of experiences and visions. It aimed to develop an informed understanding of the emerging and future directions of higher education in developed and developing countries.